The Correlation of Watching Soap Opera “Anak Jalanan” Intensity and Perceived Reality with Antisocial Behavior - Amalia, Emma; Herieningsih, MS, Dra. Sri Widowati (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
This research is based on the high number of soap operas that contain elements of violence, especially Anak Jalanan soap opera. Although the KPI has given warning repeatedly to the Anak Jalanan soap opera, but it does not provide a deterrent effect because Anak Jalanan soap opera is still live with violence content. This research aims to determine the correlation of watching soap opera “Anak Jalanan” intensity and perceived reality with antisocial behavior. The theories that are use to explain the correlation in this research are the Social Learning Theory and Model Psychology Comstock. The research used non probability sampling with purposive sampling technique, with 100 respondents. Analysis used was Kendall's Correlation Coefficient Tau_b with SPSS 16. The result of the first hypothesis test between watching soap opera Anak Jalanan intensity with antisocial behavior has a positive correlation. It is seen from the significant value of 0.000 or less than 0.01 and a correlation value of 0.541 which indicates a significant correlation between the two variables. The second hypothesis test results between perceived reality with antisocial behavior have a positive correlation. It is seen from the significant value of 0.000 or less than 0.01 and a correlation value of 0.541, indicates a significant correlation between the two variables.Conclusion test this hypothesis is the higher watching soap opera Anak Jalanan intensity, the higher the antisocial behavior and the higher the perceived reality that antisocial behavior will be higher. The researchers suggest is the authorized institution such as KPI should not extend broadcasting license if there is content that does not comply with the rules, KPAI to be more active in providing awareness and media literacy in the community to consume television wisely, and parental mediation to accompany children in consuming the content of television programs